(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The article describes the concept of investments and foreign investments. The advantages of direct import of foreign investments for the host region are shown. The impact of foreign direct and portfolio investment on the region’s economy has been studied. Decisive factors have been identified for making positive decisions about foreign investment in the region.